(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
In recent decades in Latvia and other European countries increased interest about growing protein-rich crops and especially soybeans (Glycine max). Although soybean cultivation experiments in Latvia have been carried out for some time, there is still insufficient knowledge about cultivating these plants in the country's climatic conditions. A field trials was carried out in 2018, 2019 and 2020 in the Latgale Agricultural Science Centre. The effect of three factors (A: soybean cultivar (A1 — ‘Lajma’, A2 — ‘Laulema’, A3 — ‘Merlin’, A4 — ‘Tiguan’, A5 — ‘Paradis’, A6 — ‘Touttis’); B: sowing rate (B1 — 40, B2 — 50, B3 — 60 germinable seeds per 1 m2); C: row spacing (C1 — 12.5 cm, C2 — 25 cm) on the development and yield formation of soybean was examined. The experiment was carried out in the framework of the project ‘New technologies and important to look for earlier cultivars to avoid farming risks.